Crystal structure of protoporphyrinogen IX oxidase: a key enzyme in haem and chlorophyll biosynthesis - Koch, Michael (Nature Publishing Group, 2004)
Protoporphyrinogen IX oxidase (PPO), the last common enzyme of haem and chlorophyll biosynthesis, catalyses the oxidation of protoporphyrinogen IX to protoporphyrin IX. The membrane-embedded flavoprotein is the target of a large class of herbicides. In humans, a defect in PPO is responsible for the dominantly inherited disease variegate porphyria. Here we present the crystal structure of mitochondrial PPO from tobacco complexed with a phenyl-pyrazol inhibitor. PPO forms a loosely associated dimer and folds into an FAD-binding domain of the p-hydroxybenzoate-hydrolase fold and a substrate-binding domain that enclose a narrow active site cavity beneath the FAD and an α-helical membrane-binding domain. The active site architecture suggests a specific substrate-binding mode compatible with the unusual six-electron oxidation. The membrane-binding domains can be docked onto the dimeric structure of human ferrochelatase, the next enzyme in haem biosynthesis, embedded in the opposite side of the membrane. This modelled transmembrane complex provides a structural explanation for the uncoupling of haem biosynthesis observed in variegate porphyria patients and in plants after inhibiting PPO.